Does mixed vs separate sheep and cattle grazing reduce soil compaction? - Jordon, MW (Wiley, 2020)
Degradation of soil in the United Kingdom (UK) is compromising the ecosystem services that flow from this natural capital asset, including water flow regulation. Soil compacted by grazing livestock, for example, results in an increase in overland flow following rainfall and is thought to be one of the key factors contributing to increased severity of UK winter flooding in recent years. Practical farm‐scale changes in livestock management that lead to improvements in water flow regulation therefore need to be identified. This pilot study aimed to assess the impact of (i) changing stocking composition, and (ii) temporary grazing exclusions, on soil natural capital quality on a sheep and beef cattle farm in Northumberland, England. I found evidence of improved soil bulk density under mixed sheep and cattle grazing compared to cattle‐only grazing over a three‐month summer grazing season; bulk density in “cattle‐only” pastures increased from 0.836 to 0.875 g.cm‐3 from June to September 2017, compared with a small decrease of 0.875 to 0.871 g.cm‐3 in “cattle to mixed sheep and cattle” pastures (difference significant at P<0.05 level). Changing from sheep‐only grazing to mixed grazing, and exclusion of grazing, did not significantly influence bulk density change (P>0.05). This study indicates that rapid improvements in soil physical properties can be achieved through realistic changes to livestock management. If this finding can be confirmed over multiple grazing seasons, this potentially offers a straightforward means to enhance soil health on grazed land in the UK, improving delivery of water flow regulation and other ecosystem services.